2013
DOI: 10.1111/gtc.12030
|View full text |Cite
|
Sign up to set email alerts
|

TAF4b and TAF4 differentially regulate mouse embryonic stem cells maintenance and proliferation

Abstract: TAF4b is a cell type-specific subunit of the general transcription factor TFIID. Here, we show that TAF4b is highly expressed in embryonic stem cells (ESC) and is down-regulated upon differentiation. To examine the role of TAF4b in ESC, we applied a knockdown (KD) approach. TAF4b depletion is associated with morphological changes and reduced expression of the selfrenewal marker alkaline phosphatase. In contrast, KD of TAF4, a ubiquitously expressed TAF4b paralog, retained and even stabilized ESC stemness. Reti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 47 publications
(117 reference statements)
1
15
1
1
Order By: Relevance
“…In contrast, Bahat et al . 44 used siRNA knockdown and reported that Taf4b plays a critical role in maintaining ES cell stemness, whereas Taf4 knockdown had no effect. Thus, there are conflicting data on the role of Taf4 and Taf4b in maintaining ESC pluripotency, perhaps related to the techniques used or the efficiencies of knockdown achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Bahat et al . 44 used siRNA knockdown and reported that Taf4b plays a critical role in maintaining ES cell stemness, whereas Taf4 knockdown had no effect. Thus, there are conflicting data on the role of Taf4 and Taf4b in maintaining ESC pluripotency, perhaps related to the techniques used or the efficiencies of knockdown achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Bahat et al recently reported that the TAF4 paralog TAF4B is highly expressed in mESCs and is downregulated upon differentiation (55). We have independently observed the reduction of TAF1, TAF4, TAF4B, and TBP upon in vitro differentiation of mouse embryonic stem cells by RA (Figure 4B).…”
Section: Tfiid As a Direct Regulator Of Cellular Differentiation Statesmentioning
confidence: 99%
“…Moreover, the Bahat et al study reveals that TAF4B knockdown decreases mESC self-renewal, differentiation, and cell cycle progression, along with a reduction in genes that are also reduced upon RA-induced mESC differentiation. Conversely, they report TAF4 knockdown to increase proliferation and prevent RA-induced differentiation (55), suggesting functional differences between these paralogs in mESCs. Mengus et al report an increase in serum-independent autocrine growth upon TAF4 knockdown in MEFs, which they attribute to compensation by TAF4B (56), suggesting some functional overlap between these paralogs.…”
Section: Tfiid As a Direct Regulator Of Cellular Differentiation Statesmentioning
confidence: 99%
“…A TS mutation in CCG1/TAF1 in hamster cells provokes G 1 /S arrest (Sekiguchi et al, 1991), and TAF9 inactivation in chicken DT40 cells causes cell cycle arrest and apoptosis (Chen and Manley, 2000). Mouse cells that lacked TAF10 were found to be blocked in the G 1 /G 0 phase and underwent apoptosis (Metzger et al, 1999), and a subset of TAF4b-target genes preferentially expressed in embryonic stem cells to be involved in cell cycle control (Bahat et al, 2013). Studies have also indicated that TAFs could interact with specific transcription factors (Reeves and Hahn, 2005; Garbett et al, 2007), transcription activators (Rojo Niersbach et al, 1999; Asahara et al, 2001), and components involved in epigenetic modification (Jacobson et al, 2000; Lindner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%